The influence of human resource competence, internal control systems, and technology utilization on the quality of financial statement information - Beda*, Maria Ignasia Dai; Asari, Hasim (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study is to investigate how information technology, internal control mechanisms, and HR competencies affect the caliber of financial reports produced by the East Nusa Tenggara Province Regional Office of the Ministry of Religion. Purposive sampling was utilized to select 50 respondents and administer Likert scale questionnaires to them in order to gather data utilizing quantitative approaches. Using SPSS version 16, several linear regression tests were used for data analysis. The findings indicate that: (1) HR competency affects financial report quality; (2) internal accounting control system has no effect on financial report quality; and (3) technology use affects report quality monetary. This study offers valuable insights into the variables affecting the accuracy of financial report data in an organizational setting.